Analisis Penghambat Sulitnya Penerapan Akad Mudharabah pada Koperasi Serba Usaha Syariah Mitra Mandiri Pratama Sei Mencirim - Putri Qhoirunnisa; Sarwo Edi; Asmaul Husna (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2022)
The purpose of this study was to find out (1) what factors hindered the difficulty of implementing mudharabah contracts at KSU Syariah Mitra Mandiri Pratama (2) to analyze what had been done by KSU Syariah Mitra Mandiri Pratama to overcome the difficulties of applying mudharabah contracts. This study used a qualitative approach with a descriptive research type. The data used are primary data obtained from direct interviews with members of the mudharabah financing and also managers of the Mitra Mandiri Pratama Sharia Multi-Business Cooperative and secondary data obtained from the second source after primary data, namely using books. In this study using data analysis techniques, namely data reduction, data presentation, drawing conclusions and verification. The results of the study show that the factors that hinder the difficulty of applying the mudharabah contract include (1) members' moral hazard behavior (2) the seriousness of the mudarib members in running a business financed by the sharia cooperative concerned (3) violation of the provisions agreed according to the agreement where members do not use funds with what is stated in the agreement or contract (4) the internal management of the mudharib company that has not been carried out professionally according to management standards agreed between sharia cooperatives and members.